MONTAGSKONZERT – DAL BLU AL VERDE - Parra Cancino, Juan; Performance with MusikFabrik Studio MusikFabrik, Köln, DE 16 September 2024 (2024)
Live Electronics
Performances with MusikFabrik. September 16, 20hrs. Studio MusikFabrik, Cologne, DEMusic by Saariaho, Nono, Kilger and Løffler
FRIS
Editorial review
Keywords: Music, Thought and Technology